Spanish Fund: subscriptions to 24th August, 1936
028-0011-001 SPANISH FUND. Subscriptions to 24th August, 1936. £. s. d. General Council 1000.0.0. Trade Unions 5581.10.0½. Trade Councils and Labour Parties 752.8.0½. Individual and Other Subscriptions 2450.18.1½. Total Subscriptions received from British Sources 9564.16.2½. Clothing Workers of America 995.10.0. International Ladies Garment Workers' Union, America 1985.12.1. TOTAL -- £12545.18.3½. Total to 30.9.36 -- £23015.18.1. 292/946/28/11